Eficiencia del biofiltro a base de los residuos del cultivo de maíz (Zea mays) y cacao (Theobroma cacao) para remoción de sólidos en agua - Zambrano Iza, Cesar Manuel (2019)
The research was based on evaluating the efficiency of biofilters based on corn crop residues (Zea mays) and cocoa (Theobroma cacao) in the removal of solids in water (turbidity, color, total solids, total suspended solids and pH) of effluent from a medium-scale shrimp activity located in the San Antonio community of city Chone. The construction of the experimental unit was carried out with 80cm high pvc pipes with a diameter of 10cm complemented by joints and stopcocks located in a metal base. The conditioning of the organic filter materials consisted of cleaning, drying, reducing their size, washing them by means of (chlorine disinfection) and finally they were dehydrated, and the inorganic materials were conditioned by simple washing. A completely randomized experimental design was applied, consisting of 4 treatments and 3 replicates T1 (90% corn - 10% cocoa), T2 (25% corn - 75% cocoa), T3 (75% corn - 25% cocoa) and T4 (20% corn - 20% cocoa). The characterization of the residual water showed physical conditions, which allowed the application of biofilters, significant differences were found in the treatments applied, reporting that T4 is the one that presents greater efficiency in the removal of turbidity 95%, total solids dissolved 25% and solids Suspended total 84%, the cost analysis indicated that the construction and conditioning of the most efficient filter medium is $47.89 for this it follows that biofilters are a technology that allows to improve the quality of water generating waste for its use.